Planejamento em saúde como instrumento de fortalecimento da relação ensino- serviço nas unidades de saúde - Silva, Quitéria Maria Ferreira da (2019)
This study presents the results of a study that sought to analyze the contribution of academic teaching practices in planning in decentralized processes and instruments of planning and management in the Unified Health System (SUS), in the municipality of Maceió. The qualitative research, of an exploratory modality, was carried out in three health units of the III Sanitary District of Maceió and used as methodological procedures for the data collection the documentary analysis, the focal group with preceptors of the courses of medicine and nursing of the University Center CESMAC, and a semistructured interview with managers of the units of said district. For the data systematization, the content analysis methodology was used, whose inputs allowed the organization of the results in two articles. The first article focused on participants' perceptions about the understanding of health planning and the applicability of their instruments at the local level, and the second one specifically discussed the contribution of academia to SUS planning processes. The result indicated that there is an incipient understanding of professionals and managers about health planning and that there is a gap between the institutionalized planning instruments at the central SUS level and the practices performed in the services. He also pointed out that there is an academic contribution to the theoretical production of health planning, but that the instruments disseminated in education do not sufficiently dialogue with the demands of the units. Considering the results pointed out in the research about the decentralization of health planning processes at the local level, the study presents as a product a methodological instrument for the implementation and development of health unit planning. For the incorporation of the proposal by the SMS management teams and the IES courses, the product was organized in seven stages, ranging from the dialogue with the various actors to validate the proposal, to the production of subsidies and training of multipliers in health planning.